Bridging Generations: Exploring the Role of Organizational Culture in Shaping Generation Z’s Identity in Higher Education - Burhan, Burhan; Asmiraty, Asmiraty; Sugianto, Hendi (JURNAL AL-TANZIM, 2024)
This study aims to analyze the role of local wisdom-based organizational culture in shaping the identity of Generation Z in higher education so that they can adapt to digital challenges and rapid social change. This study uses a qualitative approach with in-depth interview techniques, observation, and documentation. Data were analyzed thematically by coding, pattern identification, triangulation, and member checking to ensure the accuracy of the research data. The study results indicate that organizational culture in higher education plays an important role in guiding values and norms, helping students internalize social values, actively engage in campus activities, develop social networks, and improve social skills. Students become resilient and adapt well, aligning traditional values with modern demands. The implications of this study indicate that a solid and inclusive organizational culture can support the formation of a strong, flexible, and principled student identity amidst rapid changes in the digital era. These findings can guide educational institutions in designing policies that support the development of student character and integrity development in the digital era.